Taman Gizi dan Pembuatan Makanan Tambahan Berbasis Pangan Lokal di Posyandu Mawar Putih dalam Upaya Pencegahan Masalah Gizi Kurang: Nutrition Garden and Making of Local Food-Based Supplemental Food at Mawar Putih Integrated Health Post in an Effort to Prevent Malnutrition Problems - Widyastuti, Setyo Dwi; Dartiwen, Dartiwen; Hikmana, Entus; Rudiansyah, Rudiansyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Malnutrition occurs when the nutrients consumed do not meet the body's needs. To meet nutritional needs, you can use locally grown ingredients. In Wanantara Village, many plants can be used as basic ingredients for making additional food. The purpose of this community service is to increase the knowledge of posyandu cadres about nutrition for toddlers and various additional foods made from local foods, the availability of recipe books for making additional foods made from local foods, improve the skills of posyandu cadres in making additional foods based on local foods, enhance the knowledge of cadres in planting plants with a semi-hydroponic system, and provide a nutrition garden as a source of food ingredients. The activities carried out include providing education and training, and creating a nutrition garden. The results of this service are increased knowledge of posyandu cadres about nutrition for toddlers and various additional foods based on local foods, improved skills of cadres in making additional foods made from local foods, the availability of recipe books for making PMT, increased knowledge of cadres about planting plants with a semi-hydroponic system, and the availability of a nutrition garden. The conclusion is that there is increased knowledge of nutrition for toddlers, enhanced skills among cadres in preparing additional foods from local ingredients, and the availability of a nutrition garden.